Effect of Administering GnRH at the Time of Insemination on the Fertility of Dairy Heifers Bred at Estrus - V. E. Gomez-Leon; S. A. Paez-Hurtado; L. Smulders; T. Ohlde; E. Gamboa; L. A. Cruz Mota; N. Schrag; P. Lamberto (Kansas Agricultural Experiment Station Research Reports, 2025)
Heifer reproductive performance has gained attention from both the dairy industry and academia. Thus, strategies tested in cows have been proposed to be used in heifers at the field level. The current field trial tested the hypothesis that administering GnRH at the time of insemination would increase pregnancy per artificial insemination (P/AI) in dairy heifers bred at estrus. Using Holstein heifers (12 months and older) from a heifer yard in KS, a total of 5,809 breedings were randomized to a CONT (control, untreated) or a GNRH group (a single dose of 100 mcg of GnRH at estrus-AI). The heifers were subject to the regular reproductive program of the heifer yard, which prioritized breeding to estrus, and were randomized without any blocking factor. Pregnancy per AI (P/AI) at 45 ± 3 days post-AI was compared between CONT and GNRH groups using generalized linear models. The AI technician, AI sire, breed, and semen type (sexed and conventional) were considered in the statistical analysis. Data curation consisted of removing groups that lacked representation, and the final statistical analysis included 4,774 breedings (CONT n = 2,376 and GNRH n = 2,398). Our hypothesis was not supported by the results, as evidenced by a lack of significant difference between the P/AI of CONT (41.4 ± 3%) and GNRH (42.9 ± 3%). An interaction of group by service number was also not observed. Thus, the use of GnRH at the time of AI is not recommended in heifers bred at detected estrus under the current experimental conditions.
Keywords: estrus; ovulation; heifers; fertility